Lineamientos metodológicos para incorporar la expresión plástica en el planeamiento escolar - Castro Bonilla, Julieta (2011)
The present article is addressed to teachers that wish to add to their work method the field of expression by fine arts, even when they do not possess an ideal training in that field. It must be remembered that this is not only offered in some schools as just another subject in the learning curriculum, but also as a learning resource that the teacher may use as part of its daily plan; therefore. its acknowledgement and appraisal as such is fundamental. It is expected that the suggested outlines in the article help the "grade teacher" to develop its own sensibility y, so that his or her students may establish a contact with the diverse contents of the different areas of their curriculum in a ludic way. It is also desirable that the teacher may be able to organize and plan enjoyable lessons, so that the children taking part in the learning process may savor the expression by fine arts to the fullest.